La historia de las matemáticas como instrumento pedagógico (ING) - Protti, Orietta (2003)
In this paper we take into consideration some of the principal means useable to take advantage, from the pedagogical point of view, of the history of mathematics for its teaching and understanding at the high school and undergraduate level. As an example and as an application of such ideas, we briefly review the historical development of algebra, highlighting those aspects that can be useful to the students to become familiar with the main ideas of high school algebra.